"Acquiring Thought and Language": Toward Osip Mandelstam's Philosophy of Creation. Issue 2 (4th March 2021) - Zhukova, Olga A.
ABSTRACT: The article examines the specific features of O.E. Mandelstam's artistic and philosophical thought, the intellectual style of his poetry. For Mandelstam, poetry is a special form of man's existence in the axiological horizon of culture, a form that becomes the content and task of creative work, including its civic resonance. The philosophical reinterpretation of Mandelstam's legacy that the author proposes is linked to an understanding of his artistic work as a special form of spiritual experience, as an event in being, through which a verbal statement turns into an ideal artistic model of the world, that is, into a poetic work. Poetic consciousness has its being in the word, which is existentially colored and ethically intensive. The search for a whole, for a profound harmony, drives the poet's intuitions and determines his means of perceiving and artistically representing thought-images.